2010
DOI: 10.1002/jor.21263
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐rich plasma (PRP) impairs the craniofacial bone repair associated with its elevated TGF‐β levels and modulates the co‐expression between collagen III and α‐smooth muscle actin

Abstract: Transforming growth factor-b (TGF-b) is considered the main inducer of both the a-smooth muscle actin (a-SMA) phenotype and collagen synthesis and deposition and plays a significant role in the tissue repair and the development of fibrosis. Since the PRP constitutes an important source of TGF-b and its efficacy on the craniofacial bone repair remains controversy, the aim of this study was to evaluate the effect of PRP in the presence of levels of TGF-b on PRP samples, as well as in the presence of collagen III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 44 publications
0
28
0
1
Order By: Relevance
“…PRP contains high amounts of TGFB (up to 260 ng/ml) 36 and since all isoforms of TGFB induce chondrogenesis of mesenchymal stem cells, 22,37 it is likely that TGFB available in PRP may induce chondrogenesis of human progenitor cells. The lack of knowledge about which growth factors and at which doses exert the PRP effect is a limitation of the study.…”
Section: Discussionmentioning
confidence: 99%
“…PRP contains high amounts of TGFB (up to 260 ng/ml) 36 and since all isoforms of TGFB induce chondrogenesis of mesenchymal stem cells, 22,37 it is likely that TGFB available in PRP may induce chondrogenesis of human progenitor cells. The lack of knowledge about which growth factors and at which doses exert the PRP effect is a limitation of the study.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest effect was when b-FGF was added to L-PRP [33]. Giovanni et al on the other hand, showed in four different studies published from 2010 to 2014 that use of PRP and L-PRP in animal calvarial bone defects hindered bone deposition, enhanced fibrous tissue formation, and also enhanced type III to type I collagen ratio [34][35][36][37].…”
Section: Animal Studiesmentioning
confidence: 94%
“…chemotaxis Giovanni et al [36] Diminished bone repair, increased fibrous tissue deposition, increased type III: type I collagen ration…”
Section: Animal Studiesmentioning
confidence: 99%
“…hypothesis suggests that the greater synthesis of a platelet growth factor (TGF-β1) may induce the formation of actin myofilaments in the cells that compose the reparative sites, a fact that also contributes to the occurrence of pathological fibrosis (4).…”
Section: Discussionmentioning
confidence: 99%
“…The favorable use of PRP for osteogenesis has been substantiated on the hypothesis that the platelets produce growth factors that modulate the synthesis and deposition of extracellular matrix (ECM) and angiogenesis, and promotes chemotaxis of osteoprogenitor cells and their differentiation into osteoblasts (3). Nonetheless, despite this remarkable biological action, it has been claimed that the presence of PRP may not only impair osteogenesis, but also produce an abnormal histophenotype during craniofacial bone repair (4,5).…”
Section: Introductionmentioning
confidence: 99%